MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI KEGIATAN JEMUR HURUF KELOMPOK B TK KARYA BANRI KABUPATEN BULUKUMBA - Sri Winda Apriana; Sukmawati; M. Yusran Rahmat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Problem in this research ability language, especially the ability to master letters has not yet developed compared to other capabilities. Children look difficult at times name the letter symbols. So that tesearchers provide a solution by carrying out letter drying activities in the hope that it will make it easier for children to master language, especially the ability to recognize letters. The purpose of this research is to find out how the application of letter drying activities can improve the ability to recognize letters in group B children at Karya Banri kindergarten, Bulukumba Regency.this research is a class action research with quantitative descriptive data analysis and data collection techniques through observation an documentation. The subject of this research is group B kindergaerden of Karya Banri Bulukumba regency totalling 20 children. The results of the study showed that in the first cysle as a whole only reached 62,9% which met the sufficient criteria. While the re-doing of research in the second cycle as a whole has reached 75,5% and has met the good criteria and is at the level of ability to develop according to expectations.